Cognitive factors that affect speaking skills in English as a foreign language EFL learning. - Orrala Tomalá, Yuliana Mercedes (2025)
Distraction, lack of attention, and spontaneous mental disconnection are factors involved in learning a foreign language that is usually present in the classroom. The objective of the project was to investigate the importance of these factors in the teaching and learning of English. A qualitative approach methodology was used with a descriptive scope and phenomenological design, considering a certain number of teachers from the unidad educativa Eloy Velásquez Cevallos and unidad educativa José Antonio García Cando as main samples for the investigation of the research proposal, being these directly involved who provided an expensive answer based on previous experiences. This included that the teachers have knowledge about these factors and that the influences are perceived in observation regarding the development of speech being evident in behaviors such as nervousness and lack of confidence, seeing the difficulty of the linking of words which is perceived as disorderly and inadequate, so that educators include strategies that minimize the presence of mental barriers and self-analysis in the domain of pronunciation. The research concluded that despite taking into account the cognitive needs, in an environment where hours are limited, the participants show concern that carrying out a complete immersion in the language taking into account visible aspects to be considered in the students, are highlighted, but do not establish a demand for full integration based on what is perceived in the educational classroom.